EFFECTIVENESS OF TRI PRAMANA-ORIENTED SCIENCE PLAY ACTIVITY BOOK IN IMPROVING EARLY CHILDHOOD SCIENCE SKILLS - I Komang Wisnu Budi Wijaya; Ni Wayan Satri Adnyani (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to investigate the effectiveness of Tri Pramana-oriented early childhood science playbooks in improving early childhood science skills. This research is classified as descriptive quantitative research. The research was conducted at the Pratama Widyalaya Kumara Dharma Kerti education institution, Lukluk Village, Badung Regency. The total number of participants in this case was 17 (seventeen) students. The research instrument used was an observation sheet of early childhood science skills, which include the ability to classify, conduct experiments, and communicate the results of experiments. The data was analyzed descriptively. The results of the study state that the Tri Pramana-oriented early childhood science play activity book is effective in improving early childhood science skills as evidenced by more than 70% of early childhood science skills in the criteria of developing as expected. This research contributes to the development of science learning for early childhood with local wisdom, namely Tri Pramana.